Haemolysis by urea: a simple method to improve quality of pre and post stained fine needle aspiration smears - Simon, K. Ankita; Gadkari, Rasika Uday; Dattar, Sonali; Shrikhande, Anuradha Vijay (International Journal of Research in Medical Sciences, 2017)
Background: Fine needle aspiration smears may contain large amount of blood which obscures cell morphology and cause inadequacy of smears in guided aspirates and highly vascular tumors. Resolving this problem can be done by urea. Red cell lysis by urea is a simple technique without affecting the diagnostic material of smears or losing them during the procedure. To evaluate utility of urea solution for red cell lysis for improving the adequacy of prestained and Poststained smears. Methods: For prestained and Poststained slides urea concentration, time of alcohol fixation and time in urea were standardized. Ethanol fixed smears are placed in coplin jars containing urea solution and then transferred back to ethanol fixative and stained routinely. Stained smears coverslip is removed then placed in urea solution which are later transferred back to ethanol fixative and stained routinely. Conventional and urea smears are compared using scoring system by Mair et al. Results: Urea treated smears had a cleaner background when compared with conventional smears with preservation of cell morphology in ethanol fixed smears. Stastical analysis showed significant improvement in adequacy of smears after urea treatment of smears. Conclusions: The technique is reliable and applicable method to improve the adequacy of cytology smears.